Magnetic Spinels Synthesis, Properties and Applications - Singh Seehra, Mohindar (IntechOpen, 2017)
Magnetic spinels including ferrites are insulating magnetic oxides and chalcogenides with strong coupling to microwave frequencies and low eddy current losses making them indispensable for applications in wireless communications. The 13 chapters and preface of this book discuss other potential applications of magnetic spinels along with various methods used for their synthesis and their varied properties resulting from substituting different metal ions at the A and B sites. These applications include ferrofluids, anticorrosion coatings, absorber coatings for photothermal conversion, biomedicine, and environmental applications such as oxidation of volatile organic compounds and removal of arsenic and heavy metals from water. Emphasis is placed on structure-property correlations and on the nature of magnetism in spinels and their nanoparticles with current information provided for future research.